Vertical (arboreality) and horizontal (dispersal) movement increase the resilience of vertebrates to climatic instability. Issue 7 (3rd April 2017) - Scheffers, Brett. R.; Shoo, Luke; Phillips, Ben; Macdonald, Stewart L.; Anderson, Alex; VanDerWal, Jeremy; Storlie, Collin; Gourret, Arnaud; Williams, Stephen E.
Abstract: Aim: Species that respond favourably to environmental change tend to be mobile or dispersive. Living within trees has some benefits over life on the ground. Species that move vertically within forest canopies can take advantage of increased complexity and resource availability, which should correspond to increased resilience to environmental variability and change. Here we show that two modes of movement, arboreality and horizontal dispersal, across an entire bioregional vertebrate fauna in the rain forests of Australia are associated with measures of historical environmental stability. Location: Wet Tropics, Queensland, Australia. Time period: Historical (c. 20, 000 years ago) and current (1990‐2009). Major taxa studied: Mammal, bird, reptile, and frog species. Methods: We analysed vertebrate distribution for 195 species and trait data from 20 years of standardized sampling. We derived an arboreality index (i.e., the extent of vertical habitat used by each species) from a large database of field observations combined with expert opinion scores on arboreality. We compared community‐wide trends in arboreality and their horizontal dispersal potential with historical climate since the Last Glacial Maximum ( c . 20, 000 years ago) and current climate over 20 years of the recent past (1990–2009). Results: Vertical (arboreality) and horizontal (dispersal) movement were positively correlated, and both were negatively correlated with environmental stability. We found that arboreal species dominate communities in historically unstable areas, and these areas have both low richness and low endemism. Further, we show that low‐ and high‐altitude arboreal species experience similar thermal regimes, whereas low‐ and high‐altitude ground‐dwelling species experience little overlap in thermal regimes. Main conclusion: Higher variability and overlap in temperature among rain forest canopies suggests less geographical separation in tolerable conditions for arboreal taxa when compared with ground‐dwelling taxa. Increased ecological plasticity in horizontal and vertical movement as well as exposure and pre‐selection to high temperature variability appears to allow arboreal species to exploit climatically uncertain areas, a capacity that may serve them well in responding to future climate change.